SOME ASPECTS OF THE PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR THE ADAPTATION OF FUTURE TEACHERS - Sokolova, Alla; Matvieieva, Olga; Korchagina, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is devoted to the study of some aspects of psychological and pedagogical support for the adaptation of future teachers. Objective: to determine the impact of the proposed strategies of psychological and pedagogical support on the ability of students to adapt. The “Adaptability” (Multilevel Personality Questionnaire) questionnaire by A. Maklakov and S. Chermianin was used in the study to diagnose students of the 1st-6th years of bachelor’s and master’s degree programs of higher education at the faculty of arts of a pedagogical higher education establishment. The results of the introduction of strategies of psycho-pedagogical support showed that students grow their ability to regulate their interaction with the environment, that there is an increase in social contacts, social activity and self-esteem. It has been proven that the introduction of the proposed strategies of pedagogical support at the faculty of the arts of a pedagogical higher education establishment has a direct impact on the ability of students to adapt.